Solve for w 2(w-3)+5=3(w-1)

Math
2(w-3)+5=3(w-1)
Simplify 2(w-3)+5.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
2w+2⋅-3+5=3(w-1)
Multiply 2 by -3.
2w-6+5=3(w-1)
2w-6+5=3(w-1)
Add -6 and 5.
2w-1=3(w-1)
2w-1=3(w-1)
Simplify 3(w-1).
Tap for more steps…
Apply the distributive property.
2w-1=3w+3⋅-1
Multiply 3 by -1.
2w-1=3w-3
2w-1=3w-3
Move all terms containing w to the left side of the equation.
Tap for more steps…
Subtract 3w from both sides of the equation.
2w-1-3w=-3
Subtract 3w from 2w.
-w-1=-3
-w-1=-3
Move all terms not containing w to the right side of the equation.
Tap for more steps…
Add 1 to both sides of the equation.
-w=-3+1
Add -3 and 1.
-w=-2
-w=-2
Multiply each term in -w=-2 by -1
Tap for more steps…
Multiply each term in -w=-2 by -1.
(-w)⋅-1=(-2)⋅-1
Multiply (-w)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1w=(-2)⋅-1
Multiply w by 1.
w=(-2)⋅-1
w=(-2)⋅-1
Multiply -2 by -1.
w=2
w=2
Solve for w 2(w-3)+5=3(w-1)

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top